Apoptosis and miRNAs in non-alcoholic fatty liver disease pathogenesis - Sacramento Ferreira, Duarte Miguel (2013)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2013